Homogeneity analysis of wind data from 213 m high Cabauw tower. (31st January 2018) - Petrović, Predrag; Romanic, Djordje; Ćurić, Mladjen
ABSTRACT: Homogeneous meteorological data are a prerequisite for reliable climatological studies. This paper investigates the homogeneity of wind data from 213 m high Cabauw tower located in The Netherlands. The wind measurements are conducted at 10, 20, 40, 80, 140 and 200 m above ground. The analysed data cover the period from February 1986 to January 1997 and from April 2000 to December 2015. This study presents the first homogeneity analysis of wind data from a tall meteorological mast. Homogeneities of wind speed and wind direction series were investigated independently using the ReDistribution Method. Overall, the wind measurements at Cabauw tower are very homogeneous. The only wind speed inhomogeneity was detected at 200 m above ground and it seems to be, at least to a certain extent, caused by the rapid expansion of the town of Lopik in the 1990s. Lopik's growth to the west, however, only influenced the east winds on the Cabauw tower. Small inhomogeneities in wind direction data were detected at 20, 40 and 80 m levels, whereas a fairly large inhomogeneity was observed at 10 m above ground. Several potential causes of inhomogeneities in wind direction data are discussed, but the major contributor could not be determined with certainty. In addition, the homogeneity of real measurements from Cabauw tower is compared against the synthetically created wind data for Cabauw tower using the Monte‐Carlo method of random sampling. The results show that the detected anomalies are not due to the random noise in the time series. Abstract : The first homogeneity analysis of wind data from a tall meteorological tower. Wind data from the 213 m high Cabauw tower in The Netherlands have several weak wind direction inhomogeneities and a single wind speed inhomogeneity. The potential causes for inhomogeneities determined and discussed.